Organizational framework for safety in the air transport - Калюжний, Ростислав Андрійович; Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article defines the essence and purpose of forms and methods of the administrative-legal providing of the flight safety based on analysis of the legal and literary sources. Also, authors examine their characteristic, classification and methods of application.